PENGEMBANGAN KUESIONER KEBUTUHAN DAN HAMBATAN PENERAPAN ETIKET OBAT BERBASIS BRAILE - Siti Zamilatul Azkiyah; Aqidatun Naffiah Choirunniza (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2024)
Indonesia has around 1.5% or more than 3.75 million blind people. Of concern is that people with visual impairment are at high risk of medication errors. Even though there are many solutions for implementing Braille labels in daily practice, there are not many agencies that provide this service. Therefore, it is necessary to have an instrument that can measure the needs and barriers to implementing Braille etiquette. The research includes developing an instrument to measure the needs and barriers to implementing Braille etiquette in pharmaceutical services. The research instrument developed was a questionnaire with the name EKREB, which is an acronym for